Developing a bioinformatics pipeline for Urochloa spp. mapping population: from RAD sequencing data to identification of QTL for spittlebug resistance - Espitia, Paula A.; Hernández, Luis Miguel; Ryan, Camilla; Vega, Jose J. de; Jauregui, Rosa (Bioversity International and the International Center for Tropical Agriculture, 2022)
The development of molecular technologies for breeding tetraploid brachiaria interspecific hybrids (Urochloa spp.) was limited by its ploidy, the lack of a tetraploid Urochloa reference genome and the consequent drawback of using only simplex markers to construct linkage maps. However, the current increasing availability of open-source tools for genomic data in polyploid species has broadened the genetic resources that are available for the breeding of these forages. Using RAD sequencing data from a multiparenting mapping population, a new fully resolved genome of U. decumbens and phenotypical scoring for tolerance and antibiosis to Aeneolamia varia, we designed a bioinformatics pipeline to construct genetic maps that allow us to identify QTL associated with resistance to this spittlebug species. The next steps are to test different software and techniques for each phase in the pipeline, control the quality of the outputs and deliver accurate results from the phenotypic and genotypic data association.